Recomendaciones sobre vacunación en niños y adolescentes con errores innatos de la inmunidad según el programa ampliado de inmunización colombiano. - Cortés-Marín, Nathalia; Miguel Sosa-Ávila, Luis; Felipe Arias, Andrés; David Escobar-Cortés, Leonardo; Pablo Rojas-Hernández, Juan (Biomédica: Revista del Instituto Nacional de Salud)
In this manuscript, we carried out an exhaustive analysis of the global recommendations for immunization in inborn errors of immunity patients. We examined the mechanisms of action and types of vaccines, and we described the vaccines included in the Colombian immunization program together with the specific guidelines for immunization in patients with the most frequent inborn errors of immunity in Colombia. These recommendations were adjusted according to the severity and subclassifications of each immunodeficiency, considering variations in the immune response to offer evidencebased recommendations for vaccination in children with these conditions. We included the most common inborn errors of immunity worldwide and considered the vaccines included in the Colombian immunization program to avoid delays in vaccination schedules. This work was achieved through a narrative, non-systematic review of articles indexed in Spanish and English, using MeSH terms such as: "inborn errors of immunity", "primary immunodeficiencies", "vaccination in inborn errors of immunity, "types of vaccines", "mechanism of action of vaccines", and "live vaccines in inborn errors of immunity". We used search engines such as: PubMed, Medline, ScienceDirect, and websites of recognized institutions such as the Centers for Disease Control and Prevention (CDC).